Prosedur Uji Validitas Soal Bentuk Tes di Sdn Jatake 5 Kota Tangerang - Ina Magdalena; Siti Nurika Sari; Siti Najmiatul Palahiyah; Erika Helsa Febia (RC-INSTITUT, 2020)
The study aims to find out how the teacher's procedure to test the validity of the form of test questions. So far, we always see teachers only give items to students only. But we don't know what the teacher actually did before giving the item. Most validity tests are done when conducting tests and evaluating. At SDN Jatake 5 Kota Tangerang, we conducted this study aimed to find out the procedures and how to test the items. The study was conducted with a qualitative approach with interviews as a data collection technique. The results of this study indicate that the teacher's procedure in testing the validity of the test forms is very significant by analyzing the items using SPSS. But on the other hand, not all teachers test the validity of the problem because it only measures the questions through the ability of understanding during the learning process. In conclusion: the teacher's procedure for testing the validity of the form of the test is very significant and the items are declared valid.